Neopterin serum level does not reflect the disease activity in rheumatoid arthritis: A systematic review and meta‐analysis. Issue 12 (22nd October 2020) - Hejrati, Alireza; Taghadosi, Mahdi; Alizadeh‐Navaei, Reza; Hosseinzadeh, Shahnaz; Bashash, Davood; Esmaili, Mozhgan; Zafari, Parisa
Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease caused by established chronic inflammation. Neopterin levels have extensively been considered as a marker of immune activation during inflammation. In this study, we performed a systematic evaluation and meta‐analysis to elucidate the overall relationship between neopterin concentration and RA disease activity. Following the Preferred Reporting Items for Systematic Reviews and Meta‐Analysis guidelines, a systematic review was conducted using PubMed, Google Scholar, Web of Science, and Scopus from 2000 to August 2020. The Newcastle–Ottawa scale was used to assess the quality of eligible studies. The effect size (ES) and corresponding 95% confidence intervals (CIs) were calculated to evaluate this association. A total of 15 studies out of 98 met our inclusion criteria. The pooled analysis found that patients with RA had high level of neopterin; however, no statistically significant association was found between neopterin levels with high, intermediate, and low diseases activity score (DAS)‐28 (ES =11.18, 95% CI: 6.02 to 16.34, and I 2 = 91.8%; and ES = 8.57, 95% CI: 6.41 to 10.37, and I 2 = 99.5%; and ES =12.45, 95% CI: −1.68 to 26.58, and I 2 = 99.0%, respectively). Our results indicated that the neopterin concentration does not seem to have any substantial impact on the RA disease activity.